Bacterial outer membrane secretin PulD assembles and inserts into the inner membrane in the absence of its pilotin - Guilvout, Ingrid (2006)
Dodecamerization and insertion of the outer membrane secretin PulD is entirely determined by the C-terminal half of the polypeptide (PulD-CS). In the absence of its cognate chaperone PulS, PulD-CS and PulD mislocalize to the inner membrane, from which they are extractable with detergents but not urea. Electron microscopy of PulD-CS purified from the inner membrane revealed apparently normal dodecameric complexes. Electron microscopy of PulD-CS and PulD in inner membrane vesicles revealed inserted secretin complexes. Mislocalization of PulD or PulD-CS to this membrane induces the phage shock response, probably as a result of a decreased membrane electrochemical potential. Production of PulD in the absence of the phage shock response protein PspA and PulS caused a substantial drop in membrane potential and was lethal. Thus, PulD-CS and PulD assemble in the inner membrane if they do not associate with PulS. We propose that PulS prevents premature multimerization of PulD and accompanies it through the periplasm to the outer membrane. PulD is the first bacterial outer membrane protein with demonstrated ability to insert efficiently into the inner membrane.